The Effect of Hope and Self-Efficacy on Employee Burnout - Muhammad Fabian Alif; Retno Firdiyanti; Djudiyah Djudiyah (Journal of Educational, Health and Community Psychology, 2023)
The emergence of burnout can be caused by continuous work stress experienced by individuals. The occurrence of burnout can be influenced by the level of hope possessed by employees, whether employees will be able or not to perceive their goals, use goals as motivation, and prepare alternative strategies to overcome problems at work. Individuals who have good self-efficacy will see a difficult job as a challenge and prevent burnout from occurring. The purpose of this study was to determine the effect of hope and self-efficacy on burnout that occurs in employees. The sampling technique used was quota sampling. The respondents were civil servants, male and female, aged between 23 – 57 years old, who work at the Ngudi Waluyo Hospital agency, Blitar Regency as many as 150 people, including 59 administrative employees and 91 nurses. This study used SHS (State Hope Scale), the Bandura self-efficacy scale; the burnout instrument used a scale compiled by a previous researcher (Sasmita, 2016) by measuring three aspects of burnout, namely fatigue, cynicism, and inefficiency. Multiple linear regressions were used to analyze the data. The results showed that hope and self-efficacy simultaneously had an effect on burnout (17, 1%), and partially hope had a significant negative effect on burnout. However, interestingly self-efficacy had no effect on burnout.